Metode Dakwah Orang Tua Pada Anak di dalam Alquran - Muhammad Luqman El Hakim; Dasa Syawal Syahputra (Bashirah, 2022)
This study aims to determine the methods of parental Da’wah to children according to the Qur’an. This type of research is content analysis research and the approach used is a qualitative approach with a descriptive method. The data collection technique used is data coding. From this study it can be concluded that the methods of parental da’wah to children according to the Qur’an iss spread over 5 letters with a total of 14 samples of verses using 5 methods of da’wah, namely mau’izhah hasanah, testament, advice, exhortation, and discussion. The method of da’wah mau’izhah hasanah is the highest with 4 verses from 14 samples with a percentage of 28,57%. Followed by the da’wah testament method with 3 verses from 14 sample verses with a percentage of 21,43%, the da’wah method of advice with 3 verses from 14 samples with a percentage of 21,43%, then the exhortation da’wah method with 3 verses from 14 sample verses with a percentage of 21,43%, and the least is the discussion da’wah method with 1 verse fro 14 sample verses with a percentage 7,14%.